A survey of the perceptions and knowledge of anaesthesia and anaesthetists possessed by Grade 12 learners in four Johannesburg districts - Talane, Pulane Adelice (University of the Witwatersrand, Johannesburg, 2022)
Background William J.G Morton (1816-1868) introduced the world to modern anaesthesia when he successfully anaesthetised a patient using Ether at Massachusetts General Hospital in Boston in October 1846. (1) Since then, advances in pharmacology have resulted in the safer use of anaesthetic drugs and technological advances have improved monitoring of patients under anaesthesia. Anaesthetists around the world are now involved in the fields of critical care, trauma and pain management. (2)This has brought a sense professional esprit de corps to the anaesthetic fraternity. Despite this radical growth and development of the speciality, there is still a lack of public knowledge regarding the discipline of anaesthesia, anaesthetists’ expertise, or the role played by the anaesthetist in the chain of health care delivery. (3) Methods A cross sectional study was carried out between June and September 2021 on Grade 12 learners in four Johannesburg districts. A questionnaire consisting of three sections and 26 questions was handed out at pre-selected schools. The first part of the questionnaire acquired demographic data, the second contained questions pertaining to anaesthetists and anaesthesia as a speciality, and the third part pertained to interest in the field of anaesthesia. Results Of the 595 learners that participated in this study, 335 (56.3%) were aware that an anaesthetist administers anaesthesia in the operating room. A considerable number of learners n=344 (57,8%) believed that a nurse monitored and recorded the patient’s vital signs during surgery. Only 95 learners (16%) correctly identified all the duties of the anaesthetist outside of the theatre environment. Overall, learners fared poorly, achieving an average score of 14% for the questionnaire. However, there was a statistically significant correlation between being from a high socioeconomic background and awareness that the anaesthetist administers anaesthesia. A high socioeconomic background was defined as having a suburban residence, a household income comprising a salary instead of social grants and care givers that possessed a university degree. Knowledge regarding the intraoperative duties of the anaesthetist was still poor, regardless of the socioeconomic background of the learner. Previous exposure to anaesthesia did not improve awareness about anaesthesia among the learners. Conclusion This study has shown that awareness regarding anaesthesia and anaesthetists is still lacking despite the radical growth in the field. This lack of awareness cannot be ignored; education of the general public should be intensified in order to empower people to ask the right questions as well as make informed decisions about their perioperative care in the future. More than half of the learners in the study (58.5%) believed that good medical education can reduce the burden of health care costs and medicolegal consequences; and 70% of them would request an anaesthetist to provide them with detailed information about their anaesthetic before the start of surgery. Therefore, despite lack of awareness, the majority of the learners displayed interest and willingness to know more about anaesthesia, and grade 12 learners would be a formidable target group to direct anaesthetic education campaigns
A research report submitted in the partial fulfillment of the requirements for the degree of Master of Medicine in Anaesthesiology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022
Keywords: Survey; Perceptions; Knowledge; Anaesthesia; Anaesthetists; Learners; SDG-3: Good health and well-being